#TITLE_ALTERNATIVE# - KETUT RUDIAWAN (NIM 13103047), PANDE
Rotating machinery problem, such as excessive vibration level is causing its component to fail prematurely. This condition may affect the machine activity and can shorten its lifetime. One thing that causing excessive vibration level on the rotating machinery is due to defective rotating elements in the rolling bearing. Therefore the design, manufacturing and dynamic characteristic measurements of a rolling bearing testing set up is intending to facilitate research on vibration signatures of defective rolling bearing. This research is aimed to develop a bearing test rig which has static and dynamic loading facilities that is used to predict bearing vibration signature. This device is an improvement of the existing similar set up available in Dynamics Lab. Design evaluations are carried out by using static and normal mode analysis modules available in MSC Nastran for windows V4.5 software. Experimental evaluation are conducted using FRF, spectral map and power spectrum measurement. The result of this research indicates that the new bearing test rig has 2000 N maximum static load capacity. This value is higher compared to the maximum static load capacity of the existed that is 700 N. The FRF measurement result shows that the first natural frequency of the new bearing test rig (83 Hz) has higher value compared to its operating frequency (0-50 Hz). The result of the spectral map and power spectrum measurement are able to indicate a common phenomenon that is occurring at rotating element.